Performance enhancement of pyramid solar distiller using nanofluid integrated with v-corrugated absorber and wick: An experimental study. (5th March 2020) - Sharshir, Swellam W.; Elkadeem, M.R.; Meng, An
Highlights: A new combination of v-corrugated basin with wick and CuO nanofluid (DPDW + CuO) was investigated. The thermal efficiency of the DPDW + CuO was 60.5% compared to only 34% for TPD. The daily exergy efficiency of the DPDW + CuO was increased by 93% compared to the TPD. The DPDW + CuO get the least price of one-liter of the freshwater (0.015$) with 28% less than the TPD. Abstract: This paper aims to improve the performance of the pyramid distiller (PD) through an experimental investigation of three proposed modifications applied to the traditional pyramid distiller (TPD). First modification was called developed pyramid distiller (DPD) using v-corrugated absorbers to increase the surface area of evaporation, while the second modification (named DPDW) was implemented by inclusion of wick materials with the v-corrugated absorbers to minimize the rate of feed water, thus increasing the productivity to an appropriate value. In the third modification, which was designated (DPDW + CuO), copper oxide nanofluid with wick and v-corrugated absorbers was added to increase the thermal conductivity and absorptivity as well as minimize the specific heat of base fluid. The performance of three adaptations was compared to TPD, to characterize the thermal performance enhancement. Moreover, a cost analysis study was conducted to evaluate the economic performance of the three proposed systems and TPD. The results show that the three modified systems have a good thermo-economic performance compared to TPD. The use of DPD, DPDW, and DPDW + CuO enhanced the total freshwater productivity by about 28.38%, 45%, and 72.95%, respectively, compared to the TPD. Further, the DPDW + CuO has the best improvement in terms of daily energy efficiency and exergy by 77.9% and 93%, respectively, compared to TPD. Finally, the cost analysis results reveal that the DPDW + CuO gives the lowest cost among all modifications and TPD.